Decrease in Local Volumetric Bone Mineral Density in Osteoarthritic Joints Is Associated with the Increase in Cartilage Damage: A Peripheral Quantitative CT Study - Tamaddon, Maryam; Chen, Shen Mao; Vanaclocha, Leyre; Hart, Alister; El-Husseiny, Moataz; Henckel, Johann; Liu, Chaozong (Frontiers in Materials, 2017)
Osteoarthritis (OA) is the most common type of arthritis and a major cause of disability in the adult population. It affects both cartilage and subchondral bone in the joints. There has been some progress in understanding the changes in subchondral bone with progression of osteoarthritis. However, local changes in subchondral bone such as microstructure or volumetric bone mineral density in connection with the defect in cartilage are relatively unexplored. To develop an effective treatment for progression of OA, it is important to understand how the physical environment provided by the subchondral bone affects the overlying cartilage. In this study we examined the volumetric bone mineral density (vBMD) distribution in the osteoarthritic joint tissues obtained from total hip replacement surgeries due to osteoarthritis, using peripheral quantitative CT (pQCT). It was found that there is a significant decrease in volumetric bone mineral density, which co-localises with the damage in the overlying cartilage. This was not limited to the subchondral bone immediately adjacent to the cartilage defect but continued in the layers below. Bone resorption and cyst formation in the OA tissues were also detected. We observed that the bone surrounding subchondral bone cysts exhibited much higher volumetric bone mineral density than that of the surrounding bones. PQCT was able to detect significant changes in vBMD between OA and non-OA samples, as well as between areas of different cartilage degeneration, which points to its potential as a technique for detection of early OA.